Anti-Toxoplasma gondii Effects of a Novel Spider Peptide XYP1 In Vitro and In Vivo - Yuan Liu; Yaqin Tang; Xing Tang; Mengqi Wu; Shengjie Hou; Xiaohua Liu; Jing Li; Meichun Deng; Shuaiqin Huang; Liping Jiang (Biomedicines, 2021)
Toxoplasmosis, caused by an obligate intracellular parasite Toxoplasma gondii, is one of the most prevalent zoonoses worldwide. Treatments for this disease by traditional drugs have shown numerous side effects, thus effective alternative anti-Toxoplasma strategies or drugs are urgently needed. In this study, a novel spider peptide, XYP1, was identified from the cDNA library of the venom gland of the spider Lycosa coelestis. Our results showed that XYP1 has potent anti-Toxoplasma activity in vitro and in vivo. Specifically, treatment with XYP1 significantly inhibited the viability, invasion and proliferation of tachyzoites with low cytotoxicity (IC50 = 38.79 μΜ) on human host cells, and increased the survival rate of mice acutely infected with T. gondii. Next, scanning electron microscopy, transmission electron microscopy and RNA sequencing were employed to further explore the functional mechanism of XYP1, and the results indicated that XYP1 causes membrane perforation, swelling and disruption of tachyzoites, which could be closely associated with differential expression of several membrane-associated proteins including HSP29. In conclusion, XYP1 may be a promising new drug candidate for the treatment of toxoplasmosis.